A Simple Mathematical Model for Calculating Household Water Usage Based on Linear Functions - Yunita Widia Putri (Science Journal Get Press, 2025)
The increasing scarcity of clean water, exacerbated by population growth and climate change, calls for effective and efficient water management, especially at the household level. This study aims to develop a simple linear mathematical model to estimate daily household water consumption based on commonly observed domestic activities. The total water usage (W) is expressed as a function of key variables such as the number of residents, shower duration, laundry frequency, and dishwashing frequency, each multiplied by an empirical coefficient. These coefficients are drawn from published data to ensure representativeness. A case study conducted on a four-member household in Bandar Lampung, Indonesia, shows an estimated daily water consumption of 631.5 liters, aligning with global benchmarks. The study concludes that this linear model provides a practical and accessible framework for estimating household water use and can serve as a foundational tool for promoting water conservation strategies and informing public policy.